2021 IEEE 12th Control and System Graduate Research Colloquium (ICSGRC) 2021
DOI: 10.1109/icsgrc53186.2021.9515257
|View full text |Cite
|
Sign up to set email alerts
|

2019 Novel Coronavirus Disease (Covid-19): Toward a Novel Design for Disinfection Robot to Combat Coronavirus (Covid-19) Using IoT Based Technology

Abstract: Coronavirus Disease 19 or well known asCovid-19 is infectious disease that attack human respirator system. This virus is contagious due to its fast transmission from small droplets that come to people that sneezing, coughing, or even talking. This virus can stay in air for long time and it also can survive on the inanimate surface things. During this time, some places like hospital, mall, and station are places where crowds gathered. People in those places have possibility to spread the virus not only through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…An IoT-based system was developed for disinfecting areas using UAVs technology ( Mohammed, Syamsudin, Hazairin et al, 2020 ). The authors implemented their system aiming to lessen the workload for maintenance staff by remotely sanitizing the areas.…”
Section: Disinfectingmentioning
confidence: 99%
“…An IoT-based system was developed for disinfecting areas using UAVs technology ( Mohammed, Syamsudin, Hazairin et al, 2020 ). The authors implemented their system aiming to lessen the workload for maintenance staff by remotely sanitizing the areas.…”
Section: Disinfectingmentioning
confidence: 99%
“…One of the potential solutions is the integration of Internet of Things (IoT) into the healthcare sector [17]. The Internet of Things is considered as one of the feasible solutions for any remote value tracking problems such as health monitoring [4][5][6][7][8][9], agriculture [10,11], transportation [12] and green technology [13]. The advancement of this technology has given a significant impact on healthcare and well-being sector especially during the COVID-19 crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Humairi et al in [7] introduced an adaptive monitoring system and model of a smart Artificial intelligence (AI) helmet for Covid-19 detection based on body temperature. A disinfection robot presented in [8] is designed to disinfect surfaces using UV-C lights. L. Priyan et al in [9[ suggested a mobile application to monitor physical distance using Bluetooth or camera module through Augmented Reality to monitor user distance from other individual.…”
Section: Introductionmentioning
confidence: 99%
“…If an uninfected person sits or stands next to an infected one, the possibility of infection will be higher particularly during breathing or being in contact with contaminated objects and then touching eyes, nose or mouth. The crowded and indoor places promote the quick spread of the virus [4][5][6][7][8]. The Automated testing robots offer high throughput and rapid tackling of lots amount of required tests simultaneously during the pandemic of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%